Copper-loaded polyurethane / bacterial cellulose micro-nano fiber as well as preparation method and application thereof

Copper-loaded polyurethane/bacterial cellulose micro-nano fibers were prepared by electrospinning and membrane liquid interface culture method, and copper ions were chelated by dopamine on its surface, solving the problem of insufficient anticoagulation of the valve matrix material in the prior art, achieving excellent anticoagulation and pro-endothelialization effects.

CN119524205APending Publication Date: 2025-02-28EAST CHINA JIAOTONG UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411726202.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing heart valve matrix materials are prone to late thrombosis problems after implantation, and the prior art is difficult to combine micro-nano fibers and copper ion coatings to effectively maintain anticoagulation.

Method used

Polyurethane microfibers were prepared by electrospinning, and micron-nano fibers were prepared by membrane-liquid interface culture method. Then, the copper-loaded polyurethane/bacterial cellulose micron-nano fibers were chelated by dopamine on the surface of the micron-nano fibers to form copper-carrying polyurethane/bacterial cellulose micron-nano fibers.

Benefits of technology

The combination of micro-nano fibers and copper ion anticoagulation effects is achieved, which significantly improves the anticoagulation performance and pro-endothelialization ability of the heart valve matrix material, reduces platelet adhesion and activation, and prolongs the coagulation time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524205A_ABST
    Figure CN119524205A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of copper-loaded polyurethane / bacterial cellulose micro-nano fibers, the copper-loaded polyurethane / bacterial cellulose micro-nano fibers are formed by in-situ interweaving of electrostatic spinning polyurethane micron fibers and nano bacterial cellulose, and copper ions Cu < 2 + > fixed through dopamine chelation are spread all over the surfaces of the micro-nano fibers; the diameter of the electrostatic spinning polyurethane micron fiber is 0.4 to 1.1 [mu] m, and the diameter of the nano bacterial cellulose is 55 to 60 nm. The micro-nano fiber prepared by the preparation method is used for a heart valve matrix material. The copper-loaded polyurethane / bacterial cellulose micro-nano fiber with excellent anticoagulation performance is obtained through combined action of a bionic micro-nano fiber structure and physiological equivalent NO generated through in-situ catalysis of copper ions on the surface of the fiber after the micro-nano fiber is firstly prepared and then Cu < 2 + > is chelated on the surface of the micro-nano fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a copper-carrying micro-nano fiber, in particular to a polyurethane / bacterial cellulose micro-nano fiber heart valve matrix material with copper ions chelated on the surface of the micro-nano fiber. Background Art

[0002] Cardiovascular disease (CVD) is currently the leading cause of death worldwide, and valvular heart disease (VHD) is a type of CVD with a higher incidence in recent years. Valve replacement is the main treatment for patients with severe valvular heart disease. However, valve replacement materials will expose some problems that cannot be ignored during clinical application, such as a certain probability of late thrombosis after implantation. Therefore, it is imperative to prepare a heart valve matrix material with excellent anticoagulant properties.

[0003] To this end, researchers have devoted a lot of effort to develop heart valve matrix materials with excellent anti-coagulation properties. In general, structure determines performance. Anatomical studies have shown that heart valves are a structure composed of dense connective tissue interwoven with each other (to resist tearing), and are mostly composed of submicron and nanofibers. This indicates that the micro-nano structure itself has good anti-coagulation and endothelialization capabilities. Studies have shown that micro-nano fibers can regulate the behavior of plasma proteins, inhibit the activation of coagulation factors, significantly reduce platelet adhesion and activation, prolong coagulation time, and reduce hemolysis rate. Micro-nano structures are conducive to the adhesion of endothelial cells and promote endothelial cell proliferation. However, simply constructing a bionic micro-nano structure is not enough to achieve the ideal rapid endothelial promotion and anti-coagulation effects.

[0004] On the other hand, the anticoagulant repair strategy on the surface of cardiovascular interventional materials is mainly to establish an anticoagulant active surface containing certain bioactive substances, such as constructing a NO-releasing coating. The construction of the NO-releasing coating can be achieved by loading copper ions with in situ catalytic ability on the surface, thereby catalyzing endogenous S-nitrosothiol (RSNO) to release nitric oxide (NO) in a controlled manner in situ to simulate endothelial function. The generated NO will be fed back to endothelial cells to enhance migration / proliferation, and the activated NO-cyclic guanosine monophosphate (cGMP) pathway will further inhibit platelet adhesion / activation.

[0005] In terms of micro-nano fibers, there are already rapid preparation methods, for example: a Chinese patent document with publication number CN108273130A and publication date July 13, 2018 discloses a three-dimensional micro-nano fiber composite scaffold and preparation method, the scaffold is composed of a three-dimensional network structure in which micron cellulose and nano bacterial cellulose are evenly distributed and interwoven and penetrated. The preparation process mainly includes: using the nano bacterial fiber scaffold prepared by the static culture method as the substrate, and using the membrane liquid interface culture method to obtain a three-dimensional micro-nano fiber composite scaffold in which micro fibers and nano fibers are interwoven and evenly distributed.

[0006] Technology for preparing NO-releasing coatings by combining copper ions with phenolic compounds such as dopamine has also been developed. For example, a Chinese patent document with publication number CN115607728A and publication date January 17, 2023 discloses a long-term catalytic release of nitric oxide and anti-coagulation coating and its preparation method. The coating is based on a metal-based biomaterial, including an anatase TiO2 nanotube layer, a metal ion layer, a dopamine layer, and a lysine / heparin / selenocystamine combination layer. The preparation method of the coating is mainly as follows: using the metal-based biomaterial as the anode, and preparing a regular TiO2 nanotube layer on its surface by electrochemical oxidation. After heat treatment, it is placed in a dopamine solution and a mixed solution of lysine / heparin / selenocystamine in turn for deposition reaction to obtain the coating.

[0007] To date, there is no technology that combines micro-nano fibers and copper ion coating to work together to maintain anticoagulant effects. Summary of the invention

[0008] In view of the above-mentioned prior art, the present invention provides a method for preparing copper-loaded polyurethane / bacterial cellulose micro-nano fibers that can be quickly constructed. The present invention first synthesizes polyurethane, then prepares micron fibers by electrospinning, and then cultures them at a membrane-liquid interface to prepare micro-nano fibers. A copper-loaded coating is prepared on the fiber surface using a dopamine solution, and the anticoagulant effect of the micro-nano fibers and copper ions is combined to successfully prepare a polyurethane / bacterial cellulose micro-nano fiber heart valve matrix material with excellent anticoagulant effect.

[0009] In order to solve the above technical problems, the present invention proposes a method for preparing copper-loaded polyurethane / bacterial cellulose micro-nano fibers, wherein the copper-loaded polyurethane / bacterial cellulose micro-nano fibers are in situ interwoven with electrospun polyurethane micron fibers and nano bacterial cellulose, and the surface of the micro-nano fibers is covered with copper ions Cu 2+ fixed by dopamine chelation. 2+ The diameter of the electrospun polyurethane microfiber is 0.4-1.1 μm, and the diameter of the nano bacterial cellulose is 55-60 nm. The specific steps are as follows:

[0010] Step 1) preparing a polyurethane microfiber membrane by electrospinning: preparing a polyurethane spinning solution with a concentration of 15-25%, and obtaining a polyurethane microfiber membrane with a pore size of 4.5±2.5 μm by electrospinning;

[0011] Step 2) preparing a polyurethane / bacterial cellulose micro-nano fiber membrane: preparing a bacterial cellulose substrate membrane with a thickness of 1.5 mm by a membrane-liquid interface culture method; then, obtaining a polyurethane / bacterial cellulose micro-nano fiber membrane by static in situ culture;

[0012] Step 3) Chelating Cu on the surface of micro-nano fibers 2+: Prepare Cu by dissolving copper-containing compounds and dopamine in a pH 8.5 buffer. 2+ The concentration of the mixture is 25-500 μM, and the micro-nano fiber membrane obtained in step 2 is immersed in the mixture, and the surface reaction chelates Cu in the dark. 2+ , the reaction time is 3 to 6 hours, and the stirring rate is 100 to 300 rpm; after the reaction, it is rinsed with deionized water for 3 times and freeze-dried to obtain copper-loaded polyurethane / bacterial cellulose micro-nano fibers.

[0013] Furthermore, the preparation method of the present invention, wherein:

[0014] In step 1), the electrospinning parameters are: spinning humidity is 30-40%, spinning temperature is 20-25°C, spinning solution flow rate is 0.010-0.012mL / min, spinning voltage is 10-15kV, receiving distance is 16-20cm, drum speed is 50-400rpm, spinning time is 8h. The organic solvent used in the spinning solution is one of dimethylformamide, dimethylacetamide and dichloromethane.

[0015] In step 2), the process of obtaining the polyurethane / bacterial cellulose micro-nano fiber membrane by static in situ culture is: ultrasonically subjecting the polyurethane micron fiber membrane obtained in step 1 to 20 to 60 minutes, and then laying it on the bacterial cellulose base membrane and letting it stand for 3 hours; adding bacterial cellulose culture medium to the polyurethane micron fiber membrane, and culturing in situ for 1 to 3 days to obtain the initial micro-nano fiber membrane; taking out the Wiener fiber membrane, placing it in deionized water at 60 to 80°C, stirring and heating, changing the water every 1 hour, and repeating 4 to 5 times; adding a 5% NaOH solution by mass, and purifying it until the material is pure white; finally, repeatedly washing with deionized water until the material is neutral, removing the base membrane to obtain the polyurethane / bacterial cellulose micro-nano fiber membrane.

[0016] In step 3), the copper-containing compound is at least one of CuSO4·5H2O and CuCl2.

[0017] In step 3), the molar concentration of dopamine in the mixed solution is 0.1-1 mg / mL, preferably, the molar concentration of dopamine is 0.1 mg / mL.

[0018] The copper-loaded polyurethane / bacterial cellulose micro-nanofibers prepared by the preparation method of the present invention have a NO release rate of 3.90±0.85×10 -10 molcm -2 min -1; The results of the mechanical properties test were tensile strength of 5.63±0.66MPa, Young's modulus of 8.40±0.87MPa, and elongation at break of 271.8±45.2%; the CCK-8 value of cell proliferation on the fifth day of the biocompatibility evaluation was 2.63±0.13, and the results of the hemolysis experiment and static coagulation included a hemolysis rate of 0.20±0.06%, a plasma prothrombin time (PT) of 52.47±1.71s, a plasma thrombin time (TT) of 58.57±0.71s, and an activated partial thromboplastin time (APTT) of 106.74±1.41s.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The copper-loaded polyurethane / bacterial cellulose micro-nano fiber prepared by the present invention is formed by interweaving micro-fibers and nano-fibers. The micro-nano fiber is first prepared and then Cu is chelated on the surface of the micro-nano fiber. 2+ The copper-loaded polyurethane / bacterial cellulose micro-nano fiber with excellent anti-coagulation performance is obtained by the combined effect of the bionic micro-nano fiber structure and the in-situ catalysis of copper ions on the fiber surface to produce physiological equivalent NO. The good anti-coagulation performance and endothelial promotion performance are the result of the combined effect of the bionic micro-nano fiber structure and the in-situ catalysis of copper ions on the fiber surface to produce physiological equivalent NO. The micro-nano fiber of the present invention can be used for heart valve matrix materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 These are SEM electron microscope photos of the polyurethane and bacterial cellulose obtained during the preparation process of Example 9.

[0022] Figure 2 The following are the surface SEM electron microscope photograph a and the cross-sectional SEM electron microscope photograph b of the polyurethane / bacterial cellulose obtained in the preparation process of Example 9.

[0023] Figure 3 These are the SEM electron microscope photo a and mapping photo b of the copper-loaded polyurethane / bacterial cellulose prepared in Example 9.

[0024] Figure 4 The mechanical properties of bacterial cellulose, polyurethane, polyurethane / bacterial cellulose and copper-loaded polyurethane / bacterial cellulose prepared in the preparation process of Example 9 are stress-strain curve a, breaking strength b, Young's modulus c and breaking elongation d.

[0025] Figure 5 This is the NO release curve of the copper-loaded polyurethane / bacterial cellulose prepared in Example 9.

[0026] Figure 6The blood compatibility of bacterial cellulose, polyurethane, polyurethane / bacterial cellulose and copper-loaded polyurethane / bacterial cellulose prepared in the preparation process of Example 9, hemolysis rate a, plasma prothrombin time b, plasma thrombin time c and activated partial thromboplastin time d.

[0027] Figure 7 These are live staining photographs of bacterial cellulose, polyurethane, polyurethane / bacterial cellulose and copper-loaded polyurethane / bacterial cellulose prepared in the preparation process of Example 9 after endothelial cells were cultured on the surfaces for 1, 3 and 5 days, respectively.

[0028] Figure 8 The proliferation of endothelial cells in Example 9 after being cultured on the surfaces of bacterial cellulose, polyurethane, polyurethane / bacterial cellulose and copper-loaded polyurethane / bacterial cellulose prepared in the preparation process of Example 9 for 1, 3 and 5 days respectively. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but the following embodiments are by no means intended to limit the present invention in any way.

[0030] Example 1

[0031] The preparation of polyurethane / bacterial cellulose micro-nano fibers comprises the following steps:

[0032] Step 1) Preparation of micron fibers by electrospinning: First, prepare a polyurethane spinning solution with a concentration of 15%, and then obtain a polyurethane micron fiber membrane with larger pores by changing the electrospinning process parameters; the spinning parameters are: spinning humidity is 30%, spinning temperature is 20°C, spinning solution flow rate is 0.010mL / min, spinning voltage is 10kV, receiving distance is 16cm; drum speed is 50rpm, and spinning time is 8h.

[0033] Step 2) In situ culture to prepare micro-nano fibers: A bacterial cellulose basement membrane with a thickness of 1.5 mm was prepared by the membrane-liquid interface culture method; the micron polyurethane membrane obtained in step 1 was ultrasonicated for 20 minutes, and then spread on the bacterial cellulose basement membrane and allowed to stand for 3 hours; bacterial cellulose culture medium was added to the polyurethane membrane, and the initial micro-nano fiber membrane was obtained by in situ culture for 1 day. The membrane was taken out and placed in 60°C deionized water with stirring and heating, and the water was changed every 1 hour, and repeated 4 to 5 times. A 5% mass fraction of NaOH solution was added and purified until the material was pure white. Finally, it was repeatedly washed with deionized water until the material was neutral, and the basement membrane was removed to obtain the polyurethane / bacterial cellulose micro-nano fiber membrane.

[0034] Step 3) Chelating Cu on the surface of micro-nano fibers 2+Preparation of copper-loaded polyurethane / bacterial cellulose micro-nanofibers: Weigh 0.32 mg of CuSO4·5H2O solid into a 250 mL beaker, weigh 5 mg of dopamine hydrochloride powder and pour it into the beaker, use a measuring cylinder to measure 50 mL of 10 mM Tris-HCl buffer solution with a pH of 8.5 and pour it into the beaker for ultrasonic dissolution to obtain Cu 2+ The micro-nano fiber membrane obtained in step 2 is immersed in the blended solution and protected from light for surface reaction to chelate Cu 2+ The reaction time was 3 h and the stirring rate was 100 rpm. After the reaction was completed, the mixture was rinsed with deionized water for 3 times and freeze-dried.

[0035] Example 2

[0036] The steps of preparing copper-loaded polyurethane / bacterial cellulose micro-nano fibers are basically the same as those in Example 1, except that:

[0037] Step 1) The process of preparing micron fibers by electrospinning is: first prepare a polyurethane spinning solution with a concentration of 25%, and then obtain a polyurethane micron fiber membrane with larger pores by changing the electrospinning process parameters; the spinning parameters are: spinning humidity is 40%, spinning temperature is 25°C, spinning solution flow rate is 0.012mL / min, spinning voltage is 15kV, receiving distance is 20cm; drum speed is 400rpm, and spinning time is 8h.

[0038] Example 3

[0039] The steps of preparing copper-loaded polyurethane / bacterial cellulose micro-nano fibers are basically the same as those in Example 1, except that:

[0040] Step 2) The process of preparing micro-nano fibers by in-situ culture is as follows: a bacterial cellulose basement membrane with a thickness of 1.5 mm is prepared by a membrane-liquid interface culture method; the micron polyurethane membrane obtained in step 1 is ultrasonicated for 60 minutes, and then laid on the bacterial cellulose basement membrane and allowed to stand for 3 hours; bacterial cellulose culture medium is added to the polyurethane membrane, and the initial micro-nano fiber membrane is obtained by in-situ culture for 3 days. The membrane is taken out and placed in 80°C deionized water for stirring and heating, and the water is changed every 1 hour, and repeated 4 to 5 times. A 5% NaOH solution is added and purified until the material is pure white. Finally, it is repeatedly washed with deionized water until the material is neutral, and the basement membrane is removed to obtain a polyurethane / bacterial cellulose micro-nano fiber membrane.

[0041] Example 4

[0042] The steps of preparing copper-loaded polyurethane / bacterial cellulose micro-nano fibers are as follows:

[0043] Step 1) The process of preparing micron fibers by electrospinning is the same as that in Example 2;

[0044] Step 2) The process of in situ culturing and preparing micro-nano fibers is the same as that in Example 3;

[0045] Step 3) Chelating Cu on the surface of micro-nano fibers 2+ The process is the same as in Example 1;

[0046] Example 5

[0047] The steps of preparing copper-loaded polyurethane / bacterial cellulose micro-nano fibers are as follows:

[0048] Step 1) The process of preparing micron fibers by electrospinning is the same as that in Example 1;

[0049] Step 2) The process of in situ culturing and preparing micro-nano fibers is the same as that in Example 1;

[0050] Step 3) Chelating Cu on the surface of micro-nano fibers 2+ The process is as follows: weigh 3.35 mg of CuCl2 solid into a 250 mL beaker, weigh 50 mg of dopamine hydrochloride powder and pour it into the beaker, use a measuring cylinder to measure 50 mL of 10 mM, pH = 8.5 Tris-HCl buffer and pour it into the beaker for ultrasonic dissolution to obtain CuCl2. 2+ The mixture solution has a concentration of 500 μM (the molar concentration of dopamine in the mixture solution is 1 mg / mL). The micro-nano fiber membrane obtained in step 2 is immersed in the mixture solution and protected from light for surface reaction to chelate Cu 2 + The reaction time was 6 h and the stirring rate was 300 rpm. After the reaction was completed, the mixture was rinsed with deionized water for 3 times and freeze-dried.

[0051] Example 6

[0052] The steps of preparing copper-loaded polyurethane / bacterial cellulose micro-nano fibers are as follows:

[0053] Step 1) The process of preparing micron fibers by electrospinning is the same as that in Example 2;

[0054] Step 2) The process of in situ culturing and preparing micro-nano fibers is the same as that in Example 1;

[0055] Step 3) Chelating Cu on the surface of micro-nano fibers 2+ The process is as follows: 1.67 mg CuCl2 solid and 3.12 mg CuSO4·5H2O solid are weighed and placed in a 250 mL beaker, 50 mg dopamine hydrochloride powder is weighed and poured into the beaker, 50 mL of 10 mM Tris-HCl buffer with a pH of 8.5 is measured with a measuring cylinder and poured into the beaker for ultrasonic dissolution to obtain Cu 2+The mixture solution has a concentration of 500 μM (the molar concentration of dopamine in the mixture solution is 1 mg / mL). The micro-nano fiber membrane obtained in step 2 is immersed in the mixture solution and protected from light for surface reaction to chelate Cu 2+ The reaction time was 6 h and the stirring rate was 300 rpm. After the reaction was completed, the mixture was rinsed with deionized water for 3 times and freeze-dried.

[0056] Example 7

[0057] The steps of preparing copper-loaded polyurethane / bacterial cellulose micro-nano fibers are as follows:

[0058] Step 1) The process of preparing micron fibers by electrospinning is the same as that in Example 1;

[0059] Step 2) The process of in-situ culturing and preparing micro-nano fibers is the same as that in Example 3:

[0060] Step 3) Chelating Cu on the surface of micro-nano fibers 2+ The process is as follows: weigh 6.25 mg of CuSO4·5H2O solid into a 250 mL beaker, weigh 50 mg of dopamine hydrochloride powder and pour it into the beaker, use a measuring cylinder to measure 50 mL of 10 mM, pH = 8.5 Tris-HCl buffer and pour it into the beaker to dissolve it by ultrasonication to obtain Cu 2+ The mixture solution has a concentration of 500 μM (the molar concentration of dopamine in the mixture solution is 1 mg / mL). The micro-nano fiber membrane obtained in step 2 is immersed in the mixture solution and protected from light for surface reaction to chelate Cu 2+ The reaction time was 6 h and the stirring rate was 300 rpm. After the reaction was completed, the mixture was rinsed with deionized water for 3 times and freeze-dried.

[0061] Example 8

[0062] The steps of preparing copper-loaded polyurethane / bacterial cellulose micro-nano fibers are as follows:

[0063] Step 1) The process of preparing micron fibers by electrospinning is the same as that in Example 2;

[0064] Step 2) The process of in situ culturing and preparing micro-nano fibers is the same as that in Example 3;

[0065] Step 3) Chelating Cu on the surface of micro-nano fibers 2+ The process is the same as in Example 3.

[0066] In the above-mentioned Examples 1-4, in step 3), the molar concentration of dopamine in the blended liquid is 0.1 mg / mL, and in Examples 5-8, in step 3), the molar concentration of dopamine in the blended liquid is 1 mg / mL. At a concentration of 1 mg / mL, uneven dopamine aggregates will be deposited on the surface of the micro-nano fibers. Therefore, the molar concentration of dopamine in the blended liquid in the present invention is preferably 0.1 mg / mL.

[0067] Example 9

[0068] Preparation of copper-loaded polyurethane / bacterial cellulose micro-nano fibers comprises the following steps:

[0069] Step 1) The process of preparing micron fibers by electrospinning is: first prepare a polyurethane spinning solution with a concentration of 20%, and then obtain a polyurethane micron fiber membrane with larger pores by changing the electrospinning process parameters; the spinning parameters are: spinning humidity is 35%, spinning temperature is 25°C, spinning solution flow rate is 0.010mL / min, spinning voltage is 12kV, receiving distance is 16cm; drum speed is 150rpm, and spinning time is 8h. Figure 1 This is the SEM electron microscope picture of the obtained micron fiber.

[0070] Step 2) The process of preparing micro-nano fibers by in-situ culture is as follows: a bacterial cellulose basement membrane with a thickness of 1.5 mm is prepared by using a membrane-liquid interface culture method. Figure 2 The SEM electron microscope photo of the nanofibers; the micron polyurethane membrane obtained in step 1 was ultrasonicated for 40 minutes, and then laid on the bacterial cellulose basement membrane and allowed to stand for 3 hours; bacterial cellulose culture medium was added to the polyurethane membrane, and the initial micro-nano fiber membrane was obtained by in-situ culture for 3 days. The membrane was taken out and placed in 80°C deionized water for stirring and heating, and the water was changed every 1 hour, and repeated 4 to 5 times. A 5% mass fraction of NaOH solution was added and purified until the material was pure white. Finally, it was repeatedly washed with deionized water until the material was neutral, and the basement membrane was removed to obtain the polyurethane / bacterial cellulose micro-nano fiber membrane.

[0071] Step 3) Chelating Cu on the surface of micro-nano fibers 2+ The process is as follows: weigh 2.50 mg of CuSO4·5H2O solid into a 250 mL beaker, weigh 5 mg of dopamine hydrochloride powder and pour it into the beaker, use a measuring cylinder to measure 50 mL of 10 mM, pH = 8.5 Tris-HCl buffer and pour it into the beaker to dissolve it by ultrasonication to obtain CuSO4·5H2O solid. 2+ The mixture solution was prepared with a concentration of 200 μM (the molar concentration of dopamine in the mixture solution was 0.1 mg / mL). The micro-nano fiber membrane obtained in step 2 was immersed in the mixture solution and subjected to surface reaction to chelate Cu in the dark. 2+ The reaction time was 4 h and the stirring rate was 120 rpm. After the reaction was completed, the mixture was rinsed with deionized water for 3 times and freeze-dried.

[0072] Example 10

[0073] Preparation of copper-loaded polyurethane / bacterial cellulose micro-nano fibers comprises the following steps:

[0074] Step 1) The process of preparing micron fibers by electrospinning is the same as that in Example 9;

[0075] Step 2) The process of in situ culturing and preparing micro-nano fibers is the same as that in Example 9;

[0076] Step 3) Chelating Cu on the surface of micro-nano fibers 2+ The process is as follows: weigh 0.32 mg of CuSO4·5H2O solid and put it into a 250 mL beaker, weigh 5 mg of dopamine hydrochloride powder and pour it into the beaker, use a measuring cylinder to measure 50 mL of 10 mM, pH = 8.5 Tris-HCl buffer and pour it into the beaker to dissolve it by ultrasonication to obtain CuSO4·5H2O solid. 2+ The mixture solution is 25 μM (the molar concentration of dopamine in the mixture solution is 0.1 mg / mL). The micro-nano fiber membrane obtained in step 2 is immersed in the mixture solution and protected from light for surface reaction to chelate Cu 2+ The reaction time was 4 h and the stirring rate was 120 rpm. After the reaction was completed, the mixture was rinsed with deionized water for 3 times and freeze-dried.

[0077] Embodiment 11

[0078] Preparation of copper-loaded polyurethane / bacterial cellulose micro-nano fibers comprises the following steps:

[0079] Step 1) The process of preparing micron fibers by electrospinning is the same as that in Example 9;

[0080] Step 2) The process of in situ culturing and preparing micro-nano fibers is the same as that in Example 9;

[0081] Step 3) Chelating Cu on the surface of micro-nano fibers 2+ The process is as follows: weigh 6.25 mg of CuSO4·5H2O solid into a 250 mL beaker, weigh 5 mg of dopamine hydrochloride powder and pour it into the beaker, use a measuring cylinder to measure 50 mL of 10 mM, pH = 8.5 Tris-HCl buffer and pour it into the beaker to dissolve it by ultrasonication to obtain Cu 2+ The mixture solution has a concentration of 500 μM (the molar concentration of dopamine in the mixture solution is 0.1 mg / mL). The micro-nano fiber membrane obtained in step 2 is immersed in the mixture solution and protected from light for surface reaction to chelate Cu 2+ The reaction time was 4 h and the stirring rate was 120 rpm. After the reaction was completed, the mixture was rinsed with deionized water for 3 times and freeze-dried.

[0082] Test Case

[0083] Including NO release evaluation, mechanical properties experiment, blood compatibility evaluation, and endothelial cell proliferation experiment.

[0084] 1. The NO release of the copper-loaded polyurethane / bacterial cellulose micro-nanofibers obtained in Examples 9, 10 and 11 was evaluated.

[0085] Three sample materials of copper-loaded polyurethane / bacterial cellulose micro-nano fiber membranes prepared in Examples 9, 10 and 11 with a diameter of 15 mm and a thickness of about 0.13 mm were taken respectively; the sample materials were placed in a 24-well plate, 1 mL of PBS solution containing GSNO and GSH at a concentration of 10 μM was added to the material, and every 10 minutes, 50 uL of the solution was taken into a 96-well plate, Griess reagent was added, and the plate was placed in an ELISA instrument to measure the absorbance, which was then converted into NO release rate according to the standard curve.

[0086] 2. Mechanical properties experiments were conducted on the copper-loaded polyurethane / bacterial cellulose micro-nanofibers obtained in Examples 9, 10 and 11.

[0087] Pure polyurethane, bacterial cellulose and polyurethane / bacterial cellulose micro-nanofibers were used as control groups, with a total of 6 sample materials. The steps are as follows: Six sample materials with a length × width of 4 cm × 1 cm were tested for mechanical properties using a microcomputer-controlled electronic universal testing machine, and the tensile speed was set to 3 cm / min.

[0088] 3. The copper-loaded polyurethane / bacterial cellulose micro-nanofibers obtained in Examples 9, 10 and 11 were subjected to hemolysis test and static coagulation test to evaluate their blood compatibility.

[0089] Pure polyurethane, bacterial cellulose and polyurethane / bacterial cellulose micro-nanofibers were used as control groups, with a total of six sample materials. The steps are as follows: 2 ) was cleaned with physiological saline and placed in a 24-well plate. 15 mL of rabbit plasma anticoagulated with fresh sodium citrate was centrifuged at 3500 rpm for 15 min in a centrifuge to obtain platelet-poor plasma (PPP). 100 μL of PPP was added to each well, incubated at 37°C for 30 min, 50 μL of incubated PPP was added to the EP tube, and 50 μL of APTT reagent was added (incubated at 37°C for 5 min before use). After incubating the EP tube at 37°C for 3 min, 50 μL of 0.025 M CaCl2 aqueous solution was added to measure the coagulation time. 50 μL of incubated PPP was added to the EP tube, 100 μL of PT reagent was added to the EP tube, and the coagulation time was measured. 50 μL of incubated PPP was added to the EP tube, 100 μL of TT reagent was added to the EP tube, and the coagulation time was measured. Each group of samples was measured 3 times, and the average value was calculated, and the results were analyzed by statistical methods. Take another 10 mL of fresh anticoagulated rabbit blood and兔血 :V PBS =4:5 dilution, add 500 μL of diluted anticoagulated rabbit blood to each sample well, incubate in a 37°C incubator for 1 hour, set up a positive control group (mixed with physiological saline and anticoagulated rabbit blood) and a negative control group (mixed with distilled water and anticoagulated rabbit blood). After incubation, take 400 μL / well of blood in a 1.5mL centrifuge tube, centrifuge at 3000rpm for 5min. Take 100 μL / well of supernatant in a 96-well plate, use the aforementioned multifunctional microplate reader to detect the absorbance (OD) value at 540nm, measure each group of samples 3 times, and calculate the average value.

[0090] 4. The copper-loaded polyurethane / bacterial cellulose micro-nanofibers obtained in Examples 9, 10 and 11 were subjected to an endothelial cell proliferation experiment.

[0091] Pure polyurethane, bacterial cellulose and polyurethane / bacterial cellulose micro-nanofibers were used as control groups, with a total of six sample materials. The steps were as follows:

[0092] Step 1): Four materials with a diameter of 15 mm and a thickness of 0.13 mm were placed in a clean bench for ultraviolet sterilization for 1 day for use.

[0093] Step 2: Inoculate the material with endothelial cells at a concentration of 1×105 cells / ml, then place in a 37°C, 5% CO2 incubator for static co-culture, change the medium every other day, and the culture period is 1 day, 3 days and 5 days respectively.

[0094] Step 3: After the materials and cells were co-cultured for 1, 3 and 5 days, the culture medium was aspirated, 200 μL of fresh culture medium containing 10% CCK-8 reagent was added to each well and then placed in a carbon dioxide incubator for 2 hours; 200 μL of the upper clear liquid was quickly transferred to a 96-well plate, and the OD value was detected at 450nm using the aforementioned multifunctional microplate reader. After the materials and cells were co-cultured in the cell culture medium for 1, 3 and 5 days, the materials were taken out and washed three times with phosphate buffered saline (PBS); then an appropriate amount of 0.1% fluorescein diacetate (FDA) was added; 1 minute later, the growth of cells on the materials was observed using a fluorescent inverted microscope.

[0095] 5. Test results

[0096] from Figure 3 It can be seen that compared with the layered micro-nanostructured scaffolds reported in the relevant literature, the micro-nano fiber composite membrane prepared in Example 9 is a micron and nano interweaving, and the fiber surface stably chelates Cu 2+ The three-dimensional mesh micro-nano fibers are interconnected and evenly distributed. Figure 4 It can be seen that the NO release rate of Example 9 at the 30th minute was 3.90±0.85×10 -10 molcm-2 min -1 The appropriate NO release rate for promoting endothelial growth in the human body is in the range of 0.5-4×10 -10 molcm - 2 min -1 , indicating that Example 9 has successfully prepared copper-loaded micro-nano fibers with a suitable NO release rate suitable for promoting endothelial growth in the human body. Table 1 shows the NO release rate test results of Examples 9 to 11 at 30 minutes.

[0097] Table 1

[0098] sample <![CDATA[NO release rate (mol cm -2 min -1 )]]> Example 9 3.90±0.85 Example 10 1.10±0.27 Embodiment 11 7.05±0.48

[0099] from Figure 5 It can be seen that the mechanical properties of Example 9 have higher breaking strength and Young's modulus than those of micron fiber membrane and nano bacterial cellulose, wherein the breaking strengths of bacterial cellulose, polyurethane, polyurethane / bacterial cellulose and copper-loaded polyurethane / bacterial cellulose are 0.98±0.11MPa, 4.86±0.49MPa, 4.77±0.39MPa and 5.63±0.66MPa, respectively, and the Young's modulus are 5.10±1.29MPa, 1.96±0.81MPa, 6.75±0.35MPa and 8.40±0.87MPa, respectively. Table 2 shows the tensile strength and Young's modulus test results of the mechanical properties experiments of Examples 9 to 11.

[0100] Table 2

[0101] sample Breaking strength(MPa) Young's modulus (MPa) Example 9 5.63±0.66 8.40±0.87 Example 10 5.11±0.71 7.37±0.58 Embodiment 11 3.82±0.60 5.86±1.18

[0102] from Figure 6 It can be seen that the coagulation performance of Example 9 is better than that of micron fiber membrane and nano bacterial cellulose. The hemolysis rates of bacterial cellulose, polyurethane, polyurethane / bacterial cellulose and copper-loaded polyurethane / bacterial cellulose are 0.65±0.03%, 0.69±0.04%, 0.48±0.06% and 0.20±0.06%, PT is 22.26±1.06s, 22.07±1.50s, 27.30±1.64s and 52.47±1.71s, TT is 26.74±1.39s, 31.72±1.03s, 37.64±0.54s and 58.57±0.71s, APTT is 56.59±0.60s, 58.57±0.71s, 65.45±1.16s and 106.74±1.41s. Table 3 shows the hemolysis rate, PT, TT and APTT test results of Examples 9 to 11.

[0103] Table 3

[0104] sample Hemolysis rate (%) PT(s) TT(s) APTT(s) Example 9 0.20±0.06 52.47±1.71 58.57±0.71 106.74±1.41 Example 10 0.47±0.03 29.58±1.27 37.64±0.54 82.51±2.25 Embodiment 11 0.67±0.04 69.30±0.84 75.34±1.09 121.76±1.46

[0105] from Figure 7 and Figure 8 It can be seen that the material of Example 9 is not cytotoxic, and the CCK-8 value of polyurethane / bacterial cellulose is higher than that of bacterial cellulose and polyurethane, while the CCK-8 value of copper-loaded polyurethane / bacterial cellulose is higher than that of polyurethane / bacterial cellulose, indicating that the micro-nano fiber composite membrane has good bioactivity and biocompatibility and is loaded with appropriate Cu. 2+ Table 4 shows the CCK-8 test results of Examples 9 to 11 on the fifth day.

[0106] Table 4

[0107] sample CCK-8 Example 9 2.63±0.12 Example 10 2.21±0.13 Embodiment 11 1.42±0.09

[0108] In the above-mentioned embodiments 9, 10 and 11, in step 3), the Cu in the mixed solution 2+ The concentrations were 200 μM, 25 μM and 500 μM respectively. The obtained micro-nano fibers can catalyze the release of NO and 2+ When the concentration is 200 μM, the NO release rate of the obtained micro-nano fibers is more suitable for promoting endothelial growth in the human body; at this concentration, the mechanical properties of the obtained micro-nano fibers increase with Cu 2+ The concentration increases first and then decreases. 2+ The best mechanical properties were obtained at a concentration of 200 μM. At this concentration, the obtained micro-nano fibers had a lower hemolysis rate and good static coagulation performance. The hemolysis rate increased with the Cu 2+ The static coagulation time decreases first and then increases with the increase of Cu concentration. 2+ The concentration of Cu 2+ The concentration of 200 μM has the best blood compatibility; at this concentration, the ability of micro-nano fibers to promote endothelial cell growth increases with Cu 2+ The concentration increases first and then decreases. 2+ When the concentration was 200μM, the ability of micro-nano fibers to promote endothelial cell proliferation was the best.

[0109] Although the present invention has been described in detail above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can make many modifications without departing from the purpose of the present invention, all of which are within the protection of the present invention.

Claims

1. A method for preparing copper-loaded polyurethane / bacterial cellulose micro-nano fibers, characterized in that: The copper-loaded polyurethane / bacterial cellulose micro-nano fiber is in-situ interwoven with electrospun polyurethane micro-fiber and nano bacterial cellulose. The surface of the micro-nano fiber is covered with copper ions Cu 2+ fixed by dopamine chelation. 2+ ; The diameter of the electrospun polyurethane microfiber is 0.4 to 1.1 μm, and the diameter of the nano bacterial cellulose is 55 to 60 nm.

2. The preparation method according to claim 1, characterized in that: The specific steps are as follows: Step 1) preparing a polyurethane microfiber membrane by electrospinning: preparing a polyurethane spinning solution with a concentration of 15-25%, and obtaining a polyurethane microfiber membrane with a pore size of 4.5±2.5 μm by electrospinning; Step 2) preparing a polyurethane / bacterial cellulose micro-nano fiber membrane: preparing a bacterial cellulose substrate membrane with a thickness of 1.5 mm by a membrane-liquid interface culture method; then, obtaining a polyurethane / bacterial cellulose micro-nano fiber membrane by static in situ culture; Step 3) Chelating Cu on the surface of micro-nano fibers 2+ : Prepare Cu by dissolving copper-containing compounds and dopamine in a pH 8.5 buffer. 2+ The concentration of the mixture is 25 to 500 μM, and the micro-nano fiber membrane obtained in step 2 is immersed in the mixture, and the surface reaction chelating Cu is carried out in the dark. 2+ , the reaction time is 3 to 6 hours, and the stirring rate is 100 to 300 rpm; after the reaction, it is rinsed with deionized water for 3 times and freeze-dried to obtain copper-loaded polyurethane / bacterial cellulose micro-nano fibers.

3. The preparation method according to claim 2, characterized in that: In step 1), the parameters of electrospinning are: spinning humidity is 30-40%, spinning temperature is 20-25°C, spinning solution flow rate is 0.010-0.012mL / min, spinning voltage is 10-15kV, receiving distance is 16-20cm, drum speed is 50-400rpm, and spinning time is 8h.

4. The preparation method according to claim 3, characterized in that: In step 1), the organic solvent used in the spinning solution is one of dimethylformamide, dimethylacetamide and dichloromethane.

5. The preparation method according to claim 2, characterized in that: In step 2), the process of obtaining the polyurethane / bacterial cellulose micro-nano fiber membrane by static in-situ culture is as follows: The polyurethane microfiber membrane obtained in step 1 is ultrasonicated for 20 to 60 minutes, and then spread on a bacterial cellulose base membrane and allowed to stand for 3 hours; bacterial cellulose culture medium is added to the polyurethane microfiber membrane, and an initial micro-nano fiber membrane is obtained by in-situ culture for 1 to 3 days; the Wiener fiber membrane is taken out and placed in deionized water at 60 to 80° C., stirred and heated, and the water is changed every 1 hour, and repeated 4 to 5 times; a 5% by mass NaOH solution is added and purified until the material is pure white; finally, the material is repeatedly washed with deionized water until it is neutral, and the base membrane is removed to obtain a polyurethane / bacterial cellulose micro-nano fiber membrane.

6. The preparation method according to claim 2, characterized in that: In step 3), the copper-containing compound is at least one of CuSO4·5H2O and CuCl2.

7. The preparation method according to claim 2, characterized in that: In step 3), the molar concentration of dopamine in the mixed solution is 0.1-1 mg / mL.

8. The preparation method according to claim 7, characterized in that: In step 3), the molar concentration of dopamine in the mixed solution is 0.1 mg / mL.

9. A copper-loaded polyurethane / bacterial cellulose micro-nanofiber prepared according to any one of the preparation methods of claims 1-8, characterized in that: The NO release rate of the micro-nano fiber is 3.90±0.85×10 -10 molcm -2 min -1 ; The results of the mechanical properties test were tensile strength of 5.63±0.66MPa, Young's modulus of 8.40±0.87MPa, and elongation at break of 271.8±45.2%; the CCK-8 value of cell proliferation on the fifth day of the biocompatibility evaluation was 2.63±0.13, and the hemolysis experiment and static coagulation results included a hemolysis rate of 0.20±0.06%, a plasma prothrombin time (PT) of 52.47±1.71s, a plasma thrombin time (TT) of 58.57±0.71s, and an activated partial thromboplastin time (APTT) of 106.74±1.41s.

10. An application of copper-loaded polyurethane / bacterial cellulose micro-nanofibers, characterized in that: The micro-nano fiber as claimed in claim 9 is used for heart valve matrix material.

Citation Information

Patent Citations

  • Three-dimensional micro-nano fiber composite stent and preparation method thereof

    CN108273130A

  • Coating for long-term catalytic release of nitric oxide and anticoagulation and preparation method thereof

    CN115607728A